DISCURSIVE STRATEGIES OF NEWS PRESENTATION IN THE SELECTED ONLINE NEWSPAPERS - Mia Perlina (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
AbstractResearch on media language has still attracted a great deal of attention from discourse analysts due to the fact that the news delivered may vary, following the issues growing in society. This study, then, concentrated on the news reports regarding the issue of KPK vs. Polri conflict in three selected online newspapers, namely The Jakarta Post, the Jakarta Globe, and Tempo.Co. By adopting Bell’s (2007) work, the study analyzed the news text structure at the discourse level, where it dealt with the process of inclusion and exclusion in the headline, lead, and news scheme (contents). The data revealed that while The Jakarta Post (JP) tended to be objective in delivering the news in relation to Budi Gunawan’s case, the discursive strategy was practiced by The Jakarta Globe (JG) and Tempo through the news text structure at the discourse level. JG, in that case, gave the positive appraisal to Budi Gunawan (Polri) more than to KPK. Tempo, on the other hand, preferred to highlight the role of President Joko Widodo on Budi Gunawan’s case. In conclusion, the issue of media partiality in the news reports, especially on KPK vs. Polri conflict, can still be found even though it exactly opposes to journalism ethics and standards. Owing to this, it is suggested that media should pay more attention to the neutrality and objectivity in every news report.Keywords: CDA, Media, Partiality, Representation